The effects of social anxiety on interpersonal evaluations of warmth and dominance. (March 2016) - Rodebaugh, Thomas L.; Bielak, Tatiana; Vidovic, Vanja; Moscovitch, David A.
Highlights: Social anxiety affects how people interpret warmth and dominance in others. Most prefer warmth in others, but social anxiety weakened this tendency. The effects of social anxiety were ultimately better explained by similarity. Higher social anxiety led to more identification with others who were colder. High social anxiety may lead to conflicted preferences: warm versus similar (cold). Abstract: Social anxiety disorder is associated with interpersonal dysfunction, but it is not clear why people with the disorder feel unsatisfied with their relationships. One possibility is that higher social anxiety could lead to changes in sensitivity to interpersonal traits. We examined whether social anxiety moderates the types of interpersonal evaluations people make regarding warmth and dominance. We developed vignettes in which central characters systematically varied in dominance and warmth and asked two samples of participants (undergraduate students, n = 176, and online workers, n = 403) to rate their willingness to interact with, and the social desirability of, these characters. Participants in general reported stronger desire to interact with warmer and less dominant characters, and rated warmer and more dominant characters as being more socially desirable. People with higher social anxiety exhibited greater tolerance for colder and more submissive characters on both rated dimensions. The perceived similarity of the characters accounted for the bulk of these effects. Participants indicated a higher desire to interact with characters more similar to themselves, and people with higher social anxiety were more likely to rate submissive and cold characters as being like themselves. The results have implications for clinical interventions for social anxiety disorder.